2010
DOI: 10.5009/gnl.2010.4.1.25
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case-Control Study of a Novel Acid-Pump Antagonist and Proton-Pump Inhibitor for the Treatment of Iatrogenic Ulcers Caused by Endoscopic Submucosal Dissection

Abstract: Background/Aims: Revaprazan, a novel acid-pump antagonist, and proton-pump inhibitors (PPIs) have pH-independent effects on ulcer healing. The addition of a PPI promotes the cell restitution rate as well as vessel regeneration and maturation for ulcer repair. Revaprazan is known to protect the mucosa by increasing the prostaglandin concentration. Methods: We reviewed the medical records of patients who underwent endoscopic submucosal dissection (ESD) for gastric neoplasia at Yeungnam University Hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Therefore, recent studies have reported that colonoscopy is less effective in preventing right-sided colon cancers 77-79. However, right-sided colonic neoplasia was associated with specific patient characteristics, such as age and sex, and multiple environmental factors 80-84. Furthermore, right colonic adenomas were quite prevalent, and approximately 2/3 of the patients with any colorectal adenomas were reported as having at least one right side colonic adenoma 85.…”
Section: Postpolypectomy Colonoscopic Surveillance Guidelinesmentioning
confidence: 99%
“…Therefore, recent studies have reported that colonoscopy is less effective in preventing right-sided colon cancers 77-79. However, right-sided colonic neoplasia was associated with specific patient characteristics, such as age and sex, and multiple environmental factors 80-84. Furthermore, right colonic adenomas were quite prevalent, and approximately 2/3 of the patients with any colorectal adenomas were reported as having at least one right side colonic adenoma 85.…”
Section: Postpolypectomy Colonoscopic Surveillance Guidelinesmentioning
confidence: 99%
“…In addition to having a protective function in stomach membrane, revaprazan can control inflammation that occurs when the cultured gastric mucosa is infected with Helicobactor pylori (Yeo et al 2006). Compared to rabeprazole, another PPIs, revaparazan showed almost identical results in the post-treatment of endoscopic submucosal dissection, and no additional adverse drug reaction was reported thus far (Kim et al 2010). However, until now, there has been no study that specifically looked into the drug interaction between warfarin and revaprazan.…”
Section: Discussionmentioning
confidence: 91%
“…post-ESD bleeding, of which PPIs and H 2 RAs show the greatest efficacy. Indeed, PPIs have been reported to prevent bleeding after ESD [15][16][17][18] and to be more effective than H2RAs 8,19 . However, because the use of PPIs to prevent bleeding after ESD is not covered by medical insurance in Korea, H 2 RAs are the standard treatment.…”
Section: Discussionmentioning
confidence: 99%